Targeting Immunometabolism Mediated by CD73 Pathway in EGFR-Mutated Non-small Cell Lung Cancer: A New Hope for Overcoming Immune Resistance - Passarelli, Anna; Aieta, Michele; Sgambato, Alessandro; Gridelli, Cesare (Frontiers in Immunology, 2020)
Despite the relevant antitumor efficacy of immunotherapy in advanced non-small cell lung cancer (NSCLC), the results in patients whose cancer harbours activating epidermal growth factor receptor (EGFR) mutations are disappointing. The biological mechanisms underlying immune escape and both unresponsiveness and resistance to immunotherapy in EGFR-mutant NSCLC patients have been partially investigated. To this regard, lung cancer immune escape largely involves high amounts of adenosine within the tumor milieu with broad immunosuppressive effects. Indeed, besides immune checkpoint receptors and their ligands, other mechanisms inducing immunosuppression and including adenosine produced by ecto-nucleotidases CD39 and CD73 contribute to lung tumorigenesis and progression. Here, we review the clinical results of immune checkpoint inhibitors in EGFR-mutant NSCLC, focusing on the dynamic immune composition of EGFR-mutant tumor microenvironment. The adenosine pathway-mediated dysregulation of energy metabolism in tumor microenvironment is suggested as a potential mechanism involved in the immune escape process. Finally, we report the strong rationale for planning strategies of combination therapy with immune checkpoints blockade and adenosine signaling inhibition to overcome immune escape and immunotherapy resistance in EGFR-mutated NSCLC.